2016
DOI: 10.1089/thy.2015.0044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations and Gene Expression in Patients with Conventional Papillary Thyroid Carcinoma Carrying the BRAFV600E Mutation and BRAF Pseudogene

Abstract: These results do not support the use of the BRAF(V600E) mutation as a prognostic marker of conventional PTC. However, the association of high BRAF mRNA levels with more advanced clinical features suggests that BRAF mRNA levels might be a more useful clinical marker of PTCs, independent of the BRAF(V600E) mutation status. The correlation between BRAF-pseudogene mRNA levels and BRAF mRNA levels in PTCs is in agreement with the hypothesis that the BRAF pseudogene regulates BRAF expression during tumorigenesis by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Similar to the literature, mutually exclusive somatic alterations were found in BRAF (68% of PTC samples) and RET (12%), while RAS had no mutations [18, 45, 46]. The supervised clustering analysis of the methylation profiling revealed six PTC grouped with NT samples, two of them were BRAF V600E and one RET-PTC 3 positive.…”
Section: Discussionsupporting
confidence: 77%
“…Similar to the literature, mutually exclusive somatic alterations were found in BRAF (68% of PTC samples) and RET (12%), while RAS had no mutations [18, 45, 46]. The supervised clustering analysis of the methylation profiling revealed six PTC grouped with NT samples, two of them were BRAF V600E and one RET-PTC 3 positive.…”
Section: Discussionsupporting
confidence: 77%
“…Evidently, like the parent gene BRAF, BRAF pseudogene plays an oncogenic role by activating the MAP kinase signaling pathway, leading to the formation of tumors in nude mice. However, a recent study suggests that BRAF pseudogene mRNA levels are positively correlated with BRAF mRNA levels [ 69 ], which could be through ceRNA mechanism.…”
Section: Role Of Pseudogenes In Cancermentioning
confidence: 99%
“…Pseudogenes can regulate gene expression at multiple levels, and are involved in various biological processes, including cancer development and progression (9). The BRAF pseudogene has been shown to act as a competing endogenous RNA (ceRNA) in lymphoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudogenes can regulate gene expression at multiple levels, and are involved in various biological processes, including cancer development and progression ( 9 ). The BRAF pseudogene has been shown to act as a competing endogenous RNA (ceRNA) in lymphoma ( 10 ). Additionally, other studies have demonstrated that both pituitary tumor-transforming 3 pseudogene and protein disulfide isomerase family A member 3 pseudogene 1 are upregulated in hepatocellular carcinoma ( 11 , 12 ), while double homeobox A pseudogene (DUXAP) 8 promotes non-small cell lung cancer (NSCLC) cell proliferation and invasiveness ( 13 ).…”
Section: Introductionmentioning
confidence: 99%